HISTORY, MEMORY, AND THE ETHICAL HISTORIAN: NAVIGATING TRUTH AND INTERPRETATION IN SVETLANA ALEXIEVICH’S AND STUDS TERKEL’S WORLD WAR II NARRATIVES - Aitkozha, Luiza (Nazarbayev University School of Sciences and Humanities, 2025)
Through the collection of interviews, oral historians have been a bridge between the past and the present. This thesis compares the oral history narratives from a Belarusian author Svetlana Alexievich and an American author Studs Terkel. The capstone explores elements such as authorial goals, how the narrative structure reflects the authors ethical goals, trauma studies and its potential impact on the truthfulness of oral history and World War II events, Hayden White's theory of emplotment which looks at the organization and the order of testimonies in the books, literary interventions (metalepsis), criticism towards the authors, and chapter titles. Although both authors have been widely studied individually, there has been little comparative research on their use of literary tools in oral history. Hence, what are the differences and similarities in perspective between the two oral historians writing about the same historical event? In order to answer my research question I did a close reading of both books and used testimonies which were more or less similar as evidence. I have therefore discovered that while both Svetlana Alexievich and Studs Terkel aim to preserve history, their methods differ, revealing different approaches to memory, trauma, and historical representation. Alexievich actively intervenes and weaves her voice into her narrative, using generalizations and connecting her personal opinion to the overall interpretation of the book, therefore creating a heavy emotional narrative. Meanwhile, Terkel adopts a more detached and journalistic approach, asking leading questions and allowing the reader to observe the nuances and questions asked during the interviews. This thesis contributes to a deeper understanding of oral history, through its attention to emotional details, and challenges conventional narratives. By analyzing the methods of Alexievich and Terkel, it emphasizes the nuances of subject memory in shaping collective histories and invites further exploration into the ethical dimensions of oral history as a tool for documenting unofficial history.
Keywords: emplotment; metalepsis; Svetlana Alexievich; Studs Terkel; World War II; Trauma; Trauma theory; ethics; oral history; type of access: embargo